Analysis of The Need for Video-Based Volleyball Learning Media for High School Students - Agustina, Amelia; Aryanti, Silvi; Yusfi, Herri; Azhar, Samsul (Department of Physical Education, Sport, Health and Recreation, 2024)
The aim of this research is to analyze the need for the use of learning media in the form of video-based learning media at Senior High School Number 8 Palembang. This research uses quantitative descriptive research and is a form of survey method. The sample for this research was 88 class X students. The data collection technique used was observation and filling out questionnaires. The results of this research obtained a percentage of 95.3% in the Physical Education subject. The results of the analysis of the need for learning media in the form of videos show that in Senior High School number 8 Palembang it is very necessary. The implication of this research is that some teachers find it difficult to create educational materials, so they rarely use media to teach their students and only rely on outdated materials such as explanations and illustrations. Therefore, learning media is needed in the form of learning videos that can make it easier for teachers and students to understand volleyball learning material. The research indicate that a study of students’ requirements for the usage of video-based learning materials, especially in Physical Education subjects, is absolutely essential.